Occurrence of Foot and Mouth Disease (FMD) during 2014-2016 in cattle of Sirajganj district, Bangladesh - Giasuddin, Md; Mahmud, MS; Asari, Md Abu Musa Al; Akter, S (Jahangirnagar University Journal of Biological Sciences, 2017)
Abstract not available Jahangirnagar University J. Biol. Sci. 6(1): 45-49, 2017 (June)